Dissolution of a mineral trioxide aggregate sealer in endodontic solvents compared to conventional sealers - Hanan ALZRAIKAT; Nessrin Ahmad TAHA; Layla HASSOUNEH (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study is to evaluate the solubility of a Mineral Trioxide Aggregate sealer (MTA-Fillapex) compared with five other sealers, calcium hydroxide (Sealapex), resin (Realseal), zinc oxide-eugenol (Tubli-Seal), and two epoxy resins (AH-26 and AH-Plus), in chloroform and eucalyptoil in static and ultrasonic environments. Samples of each sealer were prepared (n = 180) and then divided into 12 groups that were immersed in solvents for 5 and 10 min in static and ultrasonic environments. The mean weight loss was determined, and the values were compared using Student's t-test, One-way ANOVA, and Tukey's HSD post-hoc test (p < 0.05). In chloroform, MTA-Fillapex, AH-26, and Sealapex displayed moderate solubility with no significant difference in dissolution (p = 0.125); however, their dissolution was significantly lower than that of AH-Plus (p < 0.001), which was almost fully dissolved after 10 minutes. Realseal was significantly less soluble than all sealers (p < 0.001). In eucalyptoil, MTA-Fillapex showed low solubility, as all of the sealers did, but Tubli-Seal was significantly more soluble than other sealers (p < 0.001). Using ultrasonic activation resulted in a significantly higher dissolution rate in chloroform for all sealers except MTA-Fillapex after 10 min (p = 0.226). In eucalyptoil, ultrasonic activation significantly increased the dissolution rate of all sealers except MTA-Fillapex after 5 and 10 min, Sealapex at 10 min, and AH-Plus at 5 min (p > 0.05). In conclusion, MTA-Fillapex was not sufficiently dissolved in either solvent. Ultrasonic activation had limited effectiveness on MTA-Fillapex dissolution, whereas it significantly increased the efficiency of solvents in dissolving a number of endodontic sealers.